Anti-Müllerian Hormone Serum Concentrations of Women With Germline BRCA1 or BRCA2 Mutations. Issue 8 (August 2016) - Phillips, Kelly-Anne; Collins, Ian M.; Milne, Roger L.; McLachlan, Sue Anne; Friedlander, Michael; Hickey, Martha; Stern, Catharyn; Hopper, John L.; Fisher, Richard; Kannemeyer, Gordon; Picken, Sandra; Smith, Charmaine D.; et al.
Abstract : (Abstracted from Hum Reprod 2016;31:1126–1132) Increased risks of female breast cancer, ovarian cancer, fallopian tube cancer, and primary peritoneal cancer have been attributed to germline mutations in the BRCA1 or BRCA2 genes. These also have an impact on ovarian reserve and fertility in women.